Outcomes after Transcatheter and Surgical Aortic Valve Replacement in Intermediate Risk Patients with Preoperative Mitral Regurgitation: Analysis of PARTNER II Randomized Cohort. Issue 4 (4th July 2018) - Malaisrie, S. Chris; Hodson, Robert W.; McAndrew, Thomas C.; Davidson, Charles; Swanson, Jeffrey; Hahn, Rebecca T.; Pibarot, Philippe; Jaber, Wael A.; Quader, Nishath; Zajarias, Alan; Svensson, Lars; George, Isaac; et al.
ABSTRACT: Background : Preoperative mitral regurgitation (MR) in patients undergoing transcatheter (TAVR) and surgical aortic valve replacement (SAVR) has been studied in high-risk cohorts. This study examines the outcomes of preoperative MR (≥ moderate) in a larger, intermediate-risk cohort. Methods : The Placement of Aortic Transcatheter Valves (PARTNER) 2A Trial randomized 2032 intermediate-risk patients with severe, symptomatic aortic stenosis to TAVR or SAVR. An ad-hoc analysis was performed on 1738 patients with baseline MR echocardiographic data. Patients were analyzed according to the degree of preoperative MR (≥ moderate versus ≤ mild). Results : At baseline, ≥ moderate MR was reported in 300 patients (17%). At 30 days, ≥ moderate MR had improved in 47% to ≤ mild. Thirty-day mortality was higher in SAVR patients with ≥ moderate MR (8.0 versus 3.5%; p  = 0.01), but this difference was not seen in TAVR (2.7 vs. 3.1%; p  = 0.78). At 2-years, the combined outcome of death (20.5 vs. 16.3%; p  = 0.07), stroke (12.9 vs. 9.0%; p  = 0.06), and rehospitalization (22.0 versus 17.4%; p  = 0.06) was higher in the ≥ moderate MR (40.4 vs. 32.6%; p  = 0.009), and similar between SAVR and TAVR (39.8 vs. 41.0%; p  = 0.89). Conclusions : Significant MR is prevalent in patients with severe AS and affects clinical outcomes after both TAVR and SAVR. SAVR patients with MR have high early risk, but the increased risk of death/stroke/rehospitalization becomes similar in both groups over time. Improvement in MR is common, especially in patients with lower ejection fraction and larger left-ventricular dimensions.